Social-motivational metacognitive strategy instruction (SMMS1): breaking the silence in language reading classes - Bromeley Philip; Koo, Yew Lie (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2006)
This paper attempts to address as far as possible the realities of prevalent "silence" among Malaysian learners. Acknowledging the fact that such "silence" has been an acceptable norm, it is recommended that the "silence" may at least partially be broken through a reading class that incorporates elements of critical pedagogy in the form of a metacognitive strategy instruction session. It is proposed that Socialmotivational Metacognitive Strategy instruction, abbreviated as SMMSI be offered as an alternative pedagogic practice for the ESL reading classroom. The SMMSI model hopes to train learners to become active co-participants in the classroom and critical meaning makers.